(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the distribution and biology of the butterfly Macroglossum stellatarum (Linnaeus, 1758). As a result of the research, data on biology, distribution and morphological description of Macroglossum stellatarum in the southern territories of the Ferghana Valley are given.